Opportunities of integrated care to improve equity for adults with complex needs: a qualitative study of case management in primary care - Catherine Hudon; Mathieu Bisson; Maud-Christine Chouinard; Grégory Moullec; Lourdes Rodriguez del Barrio; Émilie Angrignon-Girouard; Marie-Mychèle Pratte; Marie-Dominique Poirier (BMC Primary Care)
Abstract Background People living in precarious socio-economic conditions are at greater risk of developing mental and physical health disorders, and of having complex needs. This places them at risk of health inequity. Addressing social determinants of health (SDH) can contribute to reducing this inequity. Case management in primary care is an integrated care approach which could be an opportunity to better address SDH. The aim of this study is to better understand how case management in primary care may address the SDH of people with complex needs. Methods A case management program (CMP) for people with complex needs was implemented in four urban primary care clinics. A qualitative study was conducted with semi-structured interviews and a focus group with key informants (n = 24). An inductive thematic analysis was carried out to identify emerging themes. Results Primary care case managers were well-positioned to provide a holistic evaluation of the person’s situation, to develop trust with them, and to act as their advocates. These actions helped case managers to better address individuals’ unmet social needs (e.g., poor housing, social isolation, difficulty affording transportation, food, medication, etc.). Creating partnerships with the community (e.g., streetworkers) improved the capacity in assisting people with housing relocation, access to transportation, and access to care. Assuming people provide their consent, involving a significant relative or member of their community in an individualized services plan could support people in addressing their social needs. Conclusions Case management in primary care may better address SDH and improve health equity by developing a trusting relationship with people with complex needs, improving interdisciplinary and intersectoral collaboration and social support. Future research should explore ways to enhance partnerships between primary care and community organizations.